Implementasi Program Desa Suco Produktif Dalam Meningkatkan Kualitas Sumber Daya Manusia Desa Suco Kabupaten Jember - Shinta Ayu Lestari; AT. Hendrawijaya; Irliana Faiqotul Himmah (JPUS: Jurnal Pendidikan Untuk Semua, 2023)
The Suco Village Government of Jember Regency has a Productive Suco Village Program, this program is held in order to improve the quality of HR (Human Resources) in Suco Village. This program has a collaboration with PKBM Nurul Huda to provide free learning opportunities to RT and RW heads through the role of equality education. This research was conducted in Suco Village and PKBM Nurul Huda. Collecting data through observation, interviews and documentation. Data validity tests include credibility tests, transferability tests, dependability tests and objectivity tests. Data analysis consists of three components, namely data reduction, data presentation and conclusion. The results of the study stated that the Productive Suco Village program in improving the quality of HR (Human Resources) in Suco Village, Jember Regency was running quite well and was said to be successful because it saw the results of the development of learning residents as indicated by changes in knowledge and skills from before and after participating in this program.